Fire decline in dry tropical ecosystems enhances decadal land carbon sink - Yin, Yi (Nat Commun, 2020)
The terrestrial carbon sink has significantly increased in the past decades, but the underlying mechanisms are still unclear. The current synthesis of process-based estimates of land and ocean sinks requires an additional sink of 0.6 PgC yr(−1) in the last decade to explain the observed airborne fraction. A concurrent global fire decline was observed in association with tropical agriculture expansion and landscape fragmentation. Here we show that a decline of 0.2 ± 0.1 PgC yr(−1) in fire emissions during 2008–2014 relative to 2001–2007 also induced an additional carbon sink enhancement of 0.4 ± 0.2 PgC yr(−1) attributable to carbon cycle feedbacks, amounting to a combined sink increase comparable to the 0.6 PgC yr(−1) budget imbalance. Our results suggest that the indirect effects of fire, in addition to the direct emissions, is an overlooked mechanism for explaining decadal-scale changes in the land carbon sink and highlight the importance of fire management in climate mitigation.